Enhancing Brand Equity of Automotive Brands through Marketing Communications on Social Media - Adetunji, Raji Ridwan; Mohd Rashid, Sabrina; Ishak, Mohd Sobhi (2018)
Social media technologies such as; Facebook, YouTube, Twitter, and Instagram have proven to be perfect platforms for disseminating several types of marketing communications. Previous studies have demonstrated that these marketing communications on social media are significantly enhancing Consumer-Based Brand Equity (CBBE), however, researchers have not really focused on the differential effects of several types of marketing communications that are anchored by different social platforms in developing CBBE. Subsequently, the purpose of this study is to propose a framework that investigates the differential effects of social media marketing communications (social media advertising, social media sales promotion, social media interactive marketing and social media word-of-mouth) on CBBE of automotive brands. The findings revealed that Advertising, Promotion, and Word-of-Mouth have positive relationships with the CBBE of automotive brands. However, Interactive Marketing has an insignificant role in enhancing the CBBE of automotive brands.